Relations professionnelles, une histoire sans fin ? - Hervé Champin; Jean-Michel Denis; Marnix Dressen-Vagne; Catherine Vincent (La Nouvelle Revue du Travail, 2022)
Industrial relations are both a system of practices and rules in labour and employment relations and a field of research study For several years, these two fields have been undergoing a profound destabilisation, interpreted by some as a crisis. To understand the reasons for this, it is necessary to look back at the conditions and modalities of their constitution. But rather than concluding that they have disappeared, the article insists on a reconfiguration, which is also that of the productive models, institutions and actors involved.